Root causes and social consequences of birth injuries in Western Uganda. Issue 1 (26th July 2017) - Angell, Jennifer N.; Busingye, Priscilla; Ganyaglo, Gabriel Y.‐K.; Moyer, Cheryl A.
Abstract : A case series of Ugandan women with fistula and other birth injuries suggested that the root causes included social, cultural, and system‐based factors.